Różnice i podobieństwa biografii edukacyjnych młodzieży w krajach Europy Środkowo-Wschodniej - w kontekście modernizacji imitacyjnej systemów oświatowych = Differences and similarities in educational biographies of youth in the countries of Central and Eastern Europe - in the context of imitative modernization of education systems - Wasielewski, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article identifies the main directions of changes in the philosophy of education and their structural consequences for educational biographies of the young generation. The directions are a reaction to the change of the socio-political system and to the dominant global trends. Simultaneously, the authors take into consideration the process of imitating structural solutions existing in Western societies for a long time. The main aim of the article is to identify major similarities and differences typical of the countries undergoing similar developments, the common denominator for which is the collapse of communism.
Keywords: biografie edukacyjne; młodzież; modernizacja imitacyjna; kraje postkomunistyczne; educational biographies; youth; imitative modernization; post-communist countries